2005
DOI: 10.1111/j.1365-2761.2004.00586.x
|View full text |Cite
|
Sign up to set email alerts
|

The pathology of chronic erosive dermatopathy in Murray cod, Maccullochella peelii peelii (Mitchell)

Abstract: Chronic erosive dermatopathy (CED) is a disease of intensively farmed Murray cod in Australia that has been reported in association with the use of groundwater (mechanically extracted from shallow boreholes) supplies. CED results in focal ulceration of the skin overlying sensory canals of the head and flanks. Trials were conducted at an affected fish farm to study the development of the condition, both in Murray cod and in goldfish, and also to assess the reported recovery of lesions when affected fish were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 6 publications
5
25
0
7
Order By: Relevance
“…However, there was no evidence presented that the virus caused LLD. In addition, neither we, Blasiola (1989), nor Baily et al. (2005) found any evidence that an infectious agent was responsible for the LLD lesion.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, there was no evidence presented that the virus caused LLD. In addition, neither we, Blasiola (1989), nor Baily et al. (2005) found any evidence that an infectious agent was responsible for the LLD lesion.…”
Section: Discussionmentioning
confidence: 80%
“…The gross lesion we observed in channel catfish is identical to that observed in a ‘disease’ that has been most often referred to as ‘head and lateral line erosion’ or HLLE. HLLE most commonly affects certain tropical freshwater and marine aquarium fish of the families Anabantidae, Belontidae, Cichlidae, Acanthuridae and Pomacentridae (Gratzek 1988), but a grossly identical lesion has also been observed in some food fish (Möller & Anders 1986; Baily et al. 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Cytochemistry is also effective in analysing a range of disease states that affect immune cell function [19]. Therefore, the cytochemical approaches utilised here may also have useful applications to studying the diseases affecting this species, such as chronic erosive dermatopathy [32]. …”
Section: Discussionmentioning
confidence: 99%
“…Other pathology A pathological condition resembling chronic erosive dermatopathy recently described in Murray cod (Maccullochella peelii peelii) (Baily et al 2005) was often observed in juvenile sharpsnout sea breams, groupers and meagre reared in borehole water (Katharios, lab observations). The disease which has not yet been described in the literature affects 100% of the population and is not associated with mortalities.…”
Section: Mesomycetozoamentioning
confidence: 98%